Analisis Butir Soal Ujian Akhir Sekolah (UAS) Kelas X Materi Biologi SMA Negeri 2 Gorontalo - Pobela, Juliani; Hasan, Ani M.; Retnowati, Yuliana; Dama, Lilan; Mardin, Herinda; Kumaji, Syam S. (Peneliti.net, 2025)
This research aims to analyze scientific literacy competency in class x Final School Examination (UAS) questions on environmental pollution Gorontalo City 2 Public High School The approach and type of this research is descriptive qualitative. The techniques used in collecting data in this research were interview and documentation techniques. The research results obtained by researchers in the field are that there are four indicators of scientific literacy competency that were successfully analyzed in the School Final Examination (UAS) questions, namely the first indicator is an indicator that aims to identify valid scientific opinions, the first indicator is found in questions number 1,2,3,4,5,6,7,9,11,12 and 13. The second indicator is an indicator that trains students to carry out effective literature searches. The second indicator is found in questions number 2,3,6 and 11. The third indicator is found in question number 4,5,8, 10 and 11, in the third indicator students are trained in their ability to understand research design elements that can be obtained using scientific data. The fifth indicator is in question number 5, the fifth indicator aims to train students in solving problems in everyday life with quantitative skills.